pH dependence of the voltammetric response of Polyaniline - Scotto, Juliana (2017)
Voltammetric studies of Polyaniline (Pani) films were carried out in solutions of 3.7 M sulphate solutions of constant ionic strength and pH values comprised in the range between − 0.6 and 3.0. The results show that if the voltammetric results are properly corrected by capacitive currents, according to Feldberg´s model, it will be possible to obtain the potential dependence of the faradaic oxidation degree. The integrated anodic and cathodic charges are practically equal and independent of the electrolyte pH, in the range − 0.6 < pH < 2.0. The pH dependence of the current peaks is qualitatively explained by the change in the interactions between the redox centres as a consequence of the changes in their protonation.